Collaborative Governance Berbasis Nilai-Nilai Islam dalam Penguatan UMKM Desa: Kemitraan Toserba Sunan Drajat dan KDMP di Lamongan - Nashihin Nashihin; Elsa Nur Romadhoniah; Mardliyana Mardliyana (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
This study analyzes the collaborative governance model integrated with Islamic principles in strengthening village Micro, Small, and Medium Enterprises (MSMEs) through the partnership between Toserba Sunan Drajat and Koperasi Desa Merah Putih (KDMP) in Lamongan Regency. Utilizing a mixed-methods approach with a concurrent triangulation design, data were gathered from 15 MSME partners. The results show that collaborative governance implementation scored 4.123 (Good), with Trust Building (Amanah) achieving the highest score (4.320). This research maps conventional dimensions into Islamic principles: trust building as Amanah/Siddiq, face-to-face dialogue as Musyawarah, shared understanding as Ukhuwah, and institutional design as 'Adalah/At-Tawatsuq. The partnership's success is driven by the spiritual legitimacy of Pesantren Sunan Drajat, official government mandates, and a profit-sharing scheme that eliminates village capital burdens. However, challenges persist, including asymmetric bargaining power, strict product standardization, unoptimized distribution due to inactive KDMPs, and the lack of an integrated information system. While the model significantly strengthens MSMEs (score: 4.099) particularly in market access (4.400) and enterprise sustainability (4.373) it remains weak in providing direct capital access for MSMEs (3.711). Ultimately, the scatter plot analysis confirms that higher quality collaboration consistently drives stronger MSME empowerment.